Compaction trend and its implication in the overpressures estimate for the formations of the Colombian Foothills of the Eastern Plains - Mendoza, Javier Oswaldo; Bueno, Jael Andrea; Mateus, Darwin; Moreno, Luis-Eduardo (CT&F - Ciencia, Tecnología y Futuro, 2010)
The main objective of this article is to raise a hypothesis to explain the main causes of overpressure in the formations of the Tertiary sequence for the stratigraphic column of the Colombian Foothill. For this purpose it was conducted an analysis of compaction trends from the Guayabo Formation until the unit C8 of the Carbonera Formation; in the area of foreland, where the tectonic affectation has been minimal. This analysis integrates the most representative basins modeling and tectono-stratigraphic events for such sedimentary sequence. It mapped overpressure areas, comparing them with geological parameters such as the subsidence, uplift, heat flow and speeds of sedimentation, to identify relations of these parameters with the overpressure of the area. As the main result, it stresses the identification of different sedimentation and compacting rates for each tectono-stratigraphic sequence and its relationship with the overpressure of the formations. These differences are represented in specific equations presented in this work. One of the main conclusions relates the rapid uplift of the basin, occurred in mid Miocene and the lack of liberation of stresses; as one of the causes of the pressures that are currently observed.